Distortions in the Factor Market: Some General Equilibrium Estimates - de Melo, Jaime A. P. (The Review of Economics and Statistics, 1977)
The following sections are included:IntroductionMethodologyThe Empirical ResultsConclusionAppendixREFERENCES(This abstract was borrowed from another version of this item.)